PEMBERDAYAAN PEREMPUAN DALAM MASYARAKAT KONSERFATIF - Ihsan, Muhammad Alim (Musawa: Journal for Gender Studies, 2019)
Basically this title sees that women's empowerment is an effort of women's ability to access and have value for resources, economics, social politics and culture. from the concept, women are expected to be able to manage themselves in increasing self-confidence in order to take part and actively participate in every problem faced so that they are able to develop their potential or ability and self-concept. From this aspect, women's empowerment is both a process and a goal. as a process, empowerment is an activity to strength power and empowerment of weak groups in society. as a goal, empowerment refers to the situation or outcome that is wanted to be achieved by social change, society becomes culture.